Desempenho agronômico e modelos de crescimento para cultivares de alface - Carini, Fernanda (2019)
The objective of this study were to evaluate the agronomic performance of nine lettuce cultivars (Gloriosa, Pira Verde, Stella, Ceres, Grandes Lagos, Rubinela, Crocantela, Elisa and Vera), on the effect of the shade netting in spring and summer and adjust the Gompertz and Logistic models to the fresh and dry matter of leaves and fresh and dry matter of shoot shoots of lettuce and indicate the model that best describes the growth in autumn-winter, spring and summer. For the determination of the agronomic performance, ten experiments were conducted, using the soilless of cultivation in sheltered environment. In spring and summer experiments were conducted with and without shade netting. The black shade netting was used, with 18% reduction of the radiation, at 1.5 m above the culture. The nutritional supply was provided by means of recirculating nutrient solution in an automatically operated irrigation system. The following traits were evaluated: number of leaves, fresh and dry leaf matter, stem length, stem diameter, fresh and dry matter of the stem, fresh and dry matter of shoots, roots length and matter of fresh dry matter of roots. For the modeling the plants were evaluated every seven days during autumn-winter and every four days during spring and summer, using fresh and dry leaf matters and fresh and dry masses of shoot. These dependent variables were adjusted as a function of the accumulated thermal sum. We estimated the parameters of the Gompertz and Logistic models, verified the assumptions, calculated the quality indicators of fit, the critical points and quantified the parametric and intrinsic nonlinearities. The cultivars Gloriosa (autumn-winter), Grandes Lagos and Gloriosa (spring) and Crocantela and Vera (summer), present greater mass production and are the most suitable for cultivation in these seasons. The shade netting inside the protected environment did not improve the performance of the cultivars and its use is not necessary in spring and summer. The Logistic and Gompertz models present a satisfactory adjustment for the fresh and dry matter masses of leaves and for the masses of fresh and dry matter of aerial part for the lettuce cultivars Gloriosa, Pira Verde, Stella, Ceres, Grandes Lagos, Rubinela, Crocantela, Elisa e Vera. The Logistic model it is the best describe the growth of lettuce cultivars.